WSMXDiscoCast: a P2P approach for a better automation of the discovery mechanism for web service execution environment. (1st January 2011) - Aklouf, Youcef; Meghazi, Hadj Madani
Semantic web services aim to automate the use of web services by adding some annotations to these services in order to improve semantic expression of their functionalities. With the evolution of organisations web services and their widespread use, searching for them based on a distributed context has become a real challenge. A functionality-based web service discovery mechanism is then necessary since the functionalities are the most important thing partners look for. In this paper, we present an automatic, scalable, and distributed discovery mechanism for web service execution environments. Our solution is based on P2P technologies that proved their efficiency and robustness as distributed systems.